Metacognitive Skills of Pre-Service Biology Teachers: An Analysis through Laboratory Activities - Ajeng Purnama Heny; Ina Yuliana; Putu Krisna Widyantara Sujana (Pro-Life, 2025)
Metacognitive abilities are a crucial component of the learning process, significantly contributing to the effectiveness of teaching and learning, particularly in preparing future educators. Practicums, as an integral part of science learning, provide opportunities for pre-service biology teachers to practice their metacognitive skills through the process of planning experiments, solving problems, and reflecting on the experimental results. This study aimed to investigate the metacognitive awareness of biology education students in practicum lectures. The study employed a quantitative descriptive design using a survey method, without any treatment applied to the research object. The survey focused on assessing the metacognitive awareness of biology education students during practicum sessions, categorised into two key aspects: knowledge of cognition and regulation of cognition. A total of 112 students participated in this study, selected using a purposive sampling technique. The Metacognitive Awareness Inventory (MAI) was utilised as the primary instrument for data collection. The findings revealed that the knowledge of the cognition aspect achieved an average score of 80.3, classified as high. Meanwhile, the regulation of the cognition aspect scored slightly lower at 79.7, but is still categorised as high.